2013
DOI: 10.1055/s-0033-1344884
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the predictive value of the Forrest classification for peptic ulcer rebleeding and mortality: can classification be simplified?

Abstract: The Forrest classification still has predictive value for rebleeding of peptic ulcers, especially for gastric ulcers; however, it does not predict mortality. Based on these results, a simplified Forrest classification is proposed. However, further studies are needed to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 20 publications
1
44
1
7
Order By: Relevance
“…[9][10][11] The preoperative, intraoperative and postoperative factors have been assessed, and different clinical prediction rules have been proposed. [3,7,9,[11][12][13][14][15][16][17][18] Although duodenal ulcer (DU) and gastric ulcer (GU) seem to be identical diseases with a considerable overlap in both risk-factor profile and clinical manifestations, ulcer site could potentially affect outcome. However, the prognostic importance of ulcer site has not been extensively evaluated, and existing knowledge is ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The preoperative, intraoperative and postoperative factors have been assessed, and different clinical prediction rules have been proposed. [3,7,9,[11][12][13][14][15][16][17][18] Although duodenal ulcer (DU) and gastric ulcer (GU) seem to be identical diseases with a considerable overlap in both risk-factor profile and clinical manifestations, ulcer site could potentially affect outcome. However, the prognostic importance of ulcer site has not been extensively evaluated, and existing knowledge is ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…If this suspicion is correct, we have no evidence that any factor exerts effect on the delayed bleeding in SLE study 1,11. The For-rest classification is the most powerful predictor for rebleeding in ulcer disease 13. On ESD ulcers, a prospective observational investigation reported that the rebleeding rate was 8.6% in patients with high risk stigma and 0.8% with low risk stigma on SLE 12.…”
mentioning
confidence: 98%
“…Although a recent study suggested that the Forrest classification may not be accurate in predicting mortality, it remained useful to identify patients at high risk of rebleeding, especially those with Forrest IA peptic ulcers. 30 Conventional methods of endoscopic hemostasis can be divided into injection, thermal, and mechanical methods. Although endoscopic injection of epinephrine was shown to be effective in achieving initial hemostasis, 31 injection monotherapy is insufficient for definitive hemostasis and should be coupled with a second therapy to reduce rebleeding (OR 5 0.59, 95% CI 5 0.44-0.80) and surgery (OR 5 0.66, 95% CI 5 0.49-0.89).…”
Section: Endoscopic Treatmentmentioning
confidence: 99%